2019
DOI: 10.1016/j.bioelechem.2019.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Changes in nanomechanical properties and adhesion dynamics of algal cells during their growth

Abstract: Nanomechanical and structural characterizations of algal cells are of key importance for understanding their adhesion behavior at interfaces in the aquatic environment. We examine here the nanomechanical properties and adhesion dynamics of the marine, unicellular, green flagellate Dunaliella tertiolecta in laboratory culture. Mechanical properties of motile cells are hard to access while keeping cells viable, and studies to date are limited. Immobilization of negatively charged cells to a positively charged su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 42 publications
2
32
0
Order By: Relevance
“…These cells were centrifuged and washed with distilled water. The optical density was set at 0.5 for the spectrophotometer [29]. The adhesion studies were carried out using Dictyosphaerium on prepared antifouling copolymers P(SPMA-co-MMA), and comparative analysis was made by using each type of copolymer.…”
Section: Characterization and Bioassaymentioning
confidence: 99%
See 1 more Smart Citation
“…These cells were centrifuged and washed with distilled water. The optical density was set at 0.5 for the spectrophotometer [29]. The adhesion studies were carried out using Dictyosphaerium on prepared antifouling copolymers P(SPMA-co-MMA), and comparative analysis was made by using each type of copolymer.…”
Section: Characterization and Bioassaymentioning
confidence: 99%
“…Antibacterial activity against E. coli and S. aureus has been probed by the disk diffusion method, and further bacterial biofilm has been analyzed by SEM [28]. Algal biofilm for Dictyosphaerium species has been examined by optical microscopy [29]. The results of the current work are significant and provide a facile approach to develop functional antifouling polymers by optimizing transparency for potential applications in various areas including healthcare.…”
Section: Introductionmentioning
confidence: 98%
“…This unexpected behavior could derive from the surface properties of C. vulgaris in the log phase of growth. Change of surface properties during the exponential and stationary growth phases of D. tertiolecta was studied [36]. The results showed that D. tertiolecta was hydrophobic during the exponential growth phase as for the C. vulgaris .…”
Section: Resultsmentioning
confidence: 99%
“…The algal cell D. tertiolecta possesses a 9 nm thick plasma membrane modified on the surface with glycoproteins forming glycocalyx [19,36]. The nanomechanical characterization of D. tertiolecta in the exponential and stationary growth phases was studied [36].…”
Section: Comparison Of Adhesion Behavior Of Soft Particles and Ghost Vesicles At The Dmementioning
confidence: 99%
See 1 more Smart Citation